2023
DOI: 10.3390/ijms24020994
|View full text |Cite
|
Sign up to set email alerts
|

Rab44 Deficiency Induces Impaired Immune Responses to Nickel Allergy

Abstract: Rab44 was recently identified as an atypical Rab GTPase that possesses EF-hand and coiled-coil domains at the N-terminus, and a Rab-GTPase domain at the C-terminus. Rab44 is highly expressed in immune-related cells such as mast cells, macrophages, osteoclasts, and granulocyte-lineage cells in the bone marrow. Therefore, it is speculated that Rab44 is involved in the inflammation and differentiation of immune cells. However, little is known about the role of Rab44 in inflammation. In this study, we showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Consistent with the ndings of this study, previous in vivo studies have indicated that Rab44-KO mice display impaired allergic responses, such as anaphylactic responses and nickel-induced hypersensitivity [18,19]. In vitro studies on bone marrow mast cells derived from Rab44-KO mice showed reduced secretion of histamine and β-hexosaminidase compared to those from WT mice.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with the ndings of this study, previous in vivo studies have indicated that Rab44-KO mice display impaired allergic responses, such as anaphylactic responses and nickel-induced hypersensitivity [18,19]. In vitro studies on bone marrow mast cells derived from Rab44-KO mice showed reduced secretion of histamine and β-hexosaminidase compared to those from WT mice.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro studies on bone marrow mast cells derived from Rab44-KO mice showed reduced secretion of histamine and β-hexosaminidase compared to those from WT mice. Moreover, Rab44-KO mice exhibited slightly impaired production of TNF-α and interleukin-10 after LPS stimulation [19]. Genetic studies have suggested that human Rab44 is involved in immune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since osteoclasts and myotubes are multinucleated cells, Rab44 may regulate common mechanisms of cell‐cell fusion in these multinucleated cells. Moreover, Rab44‐KO mice exhibited impaired immune responses to nickel allergy and lipopolysaccharide stimulation (Noguromi et al, 2023). In Rab44‐KO mice, decreased serum levels of tumor necrosis factor α and interleukin 10 after lipopolysaccharide stimulation were observed.…”
Section: Discussionmentioning
confidence: 99%